2020
DOI: 10.1093/qjmed/hcaa090
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome in adults with chronic fatigue syndrome: a prospective study in England based on the CFS/ME National Outcomes Database

Abstract: Background: Chronic fatigue syndrome (CFS) is relatively common and disabling. Over 8000 patients attend adult services each year, yet little is known about the outcome of patients attending NHS services. Aim: Investigate the outcome of patients with CFS and what factors predict outcome. Design: Longitudinal patient cohort. Methods: We used data from six CFS/ME (myalgic encephalomyelitis) specialist services to measure changes in fatigue (Chalder Fatigue Scale), physical function (SF-36), anxiety and depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…A large cohort study of specialist services in the UK found positive outcomes such as reductions in fatigue, anxiety and depression. 12 Flo and Chalder conducted a study within routine practice and found that after cognitive behavioural therapy treatment, just under 40% of patients no longer met Oxford or Centers for Disease Control and Prevention criteria for chronic fatigue syndrome, and just under 20% were recovered, similar to rates of recovery reported in the Netherlands. 13 …”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…A large cohort study of specialist services in the UK found positive outcomes such as reductions in fatigue, anxiety and depression. 12 Flo and Chalder conducted a study within routine practice and found that after cognitive behavioural therapy treatment, just under 40% of patients no longer met Oxford or Centers for Disease Control and Prevention criteria for chronic fatigue syndrome, and just under 20% were recovered, similar to rates of recovery reported in the Netherlands. 13 …”
Section: Introductionmentioning
confidence: 62%
“… 15 Baseline physical functioning (36-item Short Form Health Survey) and increased levels of pain predicted poor outcomes in a large study across six specialist units. 12 However, duration of illness, counter-intuitively, was not a predictor of outcome regardless of setting. 12 , 16 18 …”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…This is much higher than in healthy children where between 3.6% and 16.6% will describe severe pain 8. In adult patients with CFS/ME pain is associated with worse outcomes 7 9…”
Section: Introductionmentioning
confidence: 97%